Dinamika Habitus dan Disiplin Religius Siswa Tahfiz di Madrasah Aliyah Darussholihin Sleman Yogyakarta - Mochammad Lathif Amin; Zaki Azmirrijali; Muhammad Faizal Dzulqarnain; Rufaidah Syafawani; Dian Kurnia Anggreta (Yayasan Literasi Sains Indonesia, 2026)
This study examines the dynamics of religious habitus and disciplinary practices among tahfiz students at Madrasah Aliyah Darussholihin Sleman through the lens of the sociology of education. It explores the formation of religious habitus in everyday routines, the institutional mechanisms that reproduce discipline, and the forms of student agency that emerge in response to these structures. Using a qualitative approach, data were collected through participant observation, in-depth interviews, and document analysis. The findings reveal that religious habitus is cultivated through strict daily rhythms, layered supervision, and the internalization of spiritual values embedded in the students’ bodily dispositions and consciousness. Institutional discipline is maintained through symbolic authority, reward-and-punishment systems, and horizontal social monitoring that fosters self-surveillance. Yet, disciplinary practices do not always produce passive obedience; some students negotiate or subtly resist rules they perceive as overly restrictive. The study shows that religious habitus at MA Darussholihin is inherently dialectical—generating piety and order while simultaneously containing the potential for mechanical obedience. This research contributes to the sociology of education and religion by elucidating how power, discipline, and agency intersect in shaping the religious character of tahfiz students within a contemporary Islamic educational setting.